Development of A Dual-Axis Solar Tracker with Passive Cooling for Enhanced Performance - Ayob, Ahmad Aizat; Saiman, Suhaimi (Evolution in Electrical and Electronic Engineering, 2023)
The dual-axis solar tracker system presented in this project utilizes light intensity measurements to optimize the alignment of solar panels with the sun's position. The system employs four Light Dependent Resistors (LDRs) to detect the intensity of sunlight in both the X-axis and Y-axis directions. Based on the readings from the LDRs, servo motors are controlled to adjust the position of the solar panel, enabling it to constantly face the sun for maximum energy absorption. In addition to the solar tracking functionality, the system incorporates a heat sink as a cooling mechanism. As solar panels tend to heat up during operation, the heat sink aids in dissipating excess heat, improving the overall efficiency and longevity of the solar panel. The heat sink is integrated into the system, ensuring effective cooling and thermal management. By combining solar tracking based on light intensity and the integration of a heat sink as a cooler, the proposed system enhances the performance and reliability of solar panels. The continuous alignment with the sun's position maximizes energy generation, while the heat sink mitigates the detrimental effects of overheating. This system serves as a practical solution for optimizing solar energy utilization in various applications, such as renewable energy systems, solar-powered devices, and off-grid installations.